Die deutschen Arten der Gattungen Elmis, Esolus, Oulimnius, Riolus, Aptyktophallus (Coleoptera: Dryopoidea). Genitalmorphologisch-taxonomische Studie an Dryopoidea I. - Steffan, August Wilhelm (Contributions to Entomology = Beiträge zur Entomologie, 1958)
The above publication on some genera of Dryopoidea deals with the problem of identification of their species by means of male and female genitalia with the result, that the genitalia structures were found to be useful for determination of species. Therefore particular descriptions of details of the external genitalia are given. A new genus and two new species are described and the spelling of some genera discussed. Nomenclatural ActsAptyktophallus Steffan, 1958 (Dryopoidea), gen. n.rietscheli Steffan, 1958 (Elmis), spec. n.illiesi Steffan, 1958 (Riolus), spec. n.